Identification and characterization of mRNAs of receptor-like kinases MhyGSO1 and MhyGSO2 in flowering parasitic plant Monotropa hypopitys - A. V. Shchennikova; E. Z. Kochieva; A. V. Beletsky; M. A. Filyushin; O. A. Shulga; N. V. Ravin; K. G. Skryabin (Вавиловский журнал генетики и селекции)
Plant organ formation is based on the balance of the programmed cell division and positional differentiation maintained by intercellular communication mediated by signaling molecules and receptors. In Arabidopsis thaliana, two paralogous leucine-rich repeat receptor-like kinases, GASSHO1 and GASSHO2, redundantly participate in the regulation of various root cells identity and functioning and the proper epidermis patterning. The GASSHO genes are characterized mainly in A. thaliana. Their significance in combination with the conservation of basic developmental processes justifies the study of GASSHO kinases in other plant species with different nutrition and developmental features. The aim of this work was to identify the GASSHO genes in an angiosperm plant, pinesap Monotropa hypopitys, which is a non-photosynthetic achlorophyllous mycoheterotroph. In different tissues (roots with buds, bracts, and flowers) of two individual plants at the late flowering stage, the transcriptomic data search identified 3’-partial mRNAs of two paralogous genes, MhyGASSHO1 (MhyGSO1) and MhyGSO2. Structural analysis of the encoded amino acid sequences revealed conserved domains, specific for leucine-rich repeat receptor-like kinases, in MhyGSO1, and the N-terminal leucine-rich domain in MhyGSO2. Phylogenetic analysis of MhyGASSHOs confirmed their homology with GSO1 and GSO2 kinases of the Rosids and Asterids representatives. The closest homologues of MhyGSO1 and MhyGSO2 were GSO1 and GSO2, respectively, of the Solanales members (Asterids). Quantification of the MhyGSO1 and MhyGSO2 transcripts revealed expression of both genes in flowers and bracts, and MhyGSO1 – also in roots with buds. In combination with known data about GSO1 and GSO2, it allowed us to assume the redundant activity of MhyGASSHO paralogues in signaling pathways, in particular, in response to exogenous sucrose and in development of reproductive organs and embryonic inflorescences.